Shift in disparities in hepatitis C treatment from interferon to DAA era: A population‐based cohort study. Issue 8 (20th February 2017) - Janjua, N. Z.; Islam, N.; Wong, J.; Yoshida, E. M.; Ramji, A.; Samji, H.; Butt, Z. A.; Chong, M.; Cook, D.; Alvarez, M.; Darvishian, M.; Tyndall, M.; et al.
Summary: We evaluated the shift in the characteristics of people who received interferon‐based hepatitis C virus (HCV) treatments and those who received recently introduced direct‐acting antivirals (DAAs) in British Columbia (BC), Canada. The BC Hepatitis Testers Cohort includes 1.5 million individuals tested for HCV or HIV, or reported cases of hepatitis B and active tuberculosis in BC from 1990 to 2013 linked to medical visits, hospitalization, cancer, prescription drugs and mortality data. This analysis included all patients who filled at least one prescription for HCV treatment until 31 July 2015. HCV treatments were classified as older interferon‐based treatments including pegylated interferon/ribavirin (PegIFN/RBV) with/without boceprevir or telaprevir, DAAs with RBV or PegIFN/RBV, and newer interferon‐free DAAs. Of 11 886 people treated for HCV between 2000 and 2015, 1164 (9.8%) received interferon‐free DAAs (ledipasvir/sofosbuvir: n=1075; 92.4%), while 452 (3.8%) received a combination of DAAs and RBV or PegIFN/RBV. Compared to those receiving interferon‐based treatment, people with HIV co‐infection (adjusted odds ratio [aOR]: 2.96, 95% CI: 2.31‐3.81), cirrhosis (aOR: 1.77, 95% CI: 1.45‐2.15), decompensated cirrhosis (aOR: 1.72, 95% CI: 1.31‐2.28), diabetes (aOR: 1.30, 95% CI: 1.10‐1.54), a history of injection drug use (aOR: 1.34, 95% CI: 1.09‐1.65) and opioid substitution therapy (aOR: 1.30, 95% CI: 1.01‐1.67) were more likely to receive interferon‐free DAAs. Socio‐economically marginalized individuals were significantly less likely (most deprived vs most privileged: aOR: 0.71, 95% CI: 0.58‐0.87) to receive DAAs. In conclusion, there is a shift in prescription of new HCV treatments to previously excluded groups (eg HIV‐co‐infected), although gaps remain for the socio‐economically marginalized populations.